2022
DOI: 10.1002/adfm.202110734
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Electronic and Pore Structure Modulation in Open Carbon Nanocages Enabling Efficient Electrocatalytic Production of H2O2 in Acidic Medium

Abstract: Electrochemical synthesis of hydrogen peroxide (H2O2) through 2e– oxygen reduction reaction is an effective approach to replace anthraquinone process. However, most reported electrocatalysts work effectively in alkaline medium in which H2O2 will easily decompose into water. It is still of great challenge to develop cost‐effective electrocatalysts with high activity and selectivity for electrocatalytic H2O2 production in acidic media. Herein, it is first theoretically demonstrated that the adsorption energy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…To probe the chemical state of other elements, X-ray photoelectron spectroscopy (XPS) analyses were collected (Figure D–F). The C 1s spectrum (Figure D) was deconvoluted into components at 284.5, 285.1, 286.06, 286.8, 288.9, and 291.1 eV, which were associated with CC, C–C, C–N/C-O, CN/CO, COO, and π–π* transitions, respectively. , The C 1s spectrum of N/O–C was similar to that of Co–N/O-C-0.9 wt %, with the similarity of the two samples also evident in C K-edge XAS data (Figure G). The peak around 284.7 eV is assigned to a 1s-π* transition involving sp 2 CC.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…To probe the chemical state of other elements, X-ray photoelectron spectroscopy (XPS) analyses were collected (Figure D–F). The C 1s spectrum (Figure D) was deconvoluted into components at 284.5, 285.1, 286.06, 286.8, 288.9, and 291.1 eV, which were associated with CC, C–C, C–N/C-O, CN/CO, COO, and π–π* transitions, respectively. , The C 1s spectrum of N/O–C was similar to that of Co–N/O-C-0.9 wt %, with the similarity of the two samples also evident in C K-edge XAS data (Figure G). The peak around 284.7 eV is assigned to a 1s-π* transition involving sp 2 CC.…”
mentioning
confidence: 80%
“…N K-edge XAS confirmed the presence of various N species in N/O–C, again with less nitrogen in Co–N/O-C-0.9 wt % (Figure S9). The O 1s XPS spectra (Figure F) showed peaks for Co–O (530.0 eV), CO (531.0 eV), C–O–C (532.3 eV), OC–O (533.3 eV), COOH/C–OH (534.2 eV), and adsorbed H 2 O/O 2 (536.8 eV). ,,, For Co–N/O-C-0.9 wt %, the relative oxygen speciation was C–O–C (35.0%), CO (10.7%), OC–O (21.5%), and COOH/C–OH (13.39%). For N/O–C, the corresponding values were 15.15%, 27.20%, 24.39%, and 12.66%, respectively.…”
mentioning
confidence: 99%
“…On the other hand, it appears that the addition of oxygenated species, for example to give Co-O-C, favours high selectivity for the two electron transfer reaction, as displayed in Fig. 6 [178,217]. Indeed, it has been shown using computational studies, that a lower energy barrier exists for the adsorption of *OOH on COOH-terminated carbon.…”
Section: Four and Two Electron Transfer At The Mesoporous Carbonbased...mentioning
confidence: 98%
“…Several nanoparticles and nanostructures have been successfully immobilised within MC to give impressive ORR activity and these include a number of iron-based nanostructures, including iron nanoparticles [159], Fe 3 O 4 [160,161] , Fe 2 O 3 [162], Fe/Fe 2 O 3 [163], FeCo [164], CoFe 2 O 4 [165,166], Fe 1− x S [167], Fe 3 C [168][169][170][171], FeS [172], and Fe 2 P [173,174] nanostructures. Similarly, a number of cobalt-based nanostructures have been employed, such as Co nanoparticles [175][176][177][178][179][180], single-atom-like Co with Co nanoparticles [181], CoO [182][183][184], Co/CoO [185], Co 3 O 4 [186,187], CoP [153,188], CoCu Fig. 5.…”
Section: Electrocatalysts C Precursors Electrochemical Parametersmentioning
confidence: 99%
“…201,237 Researches have demonstrated that they can achieve the simultaneous dehalogenation and oxidation of halide. 237 Because oxygen can be cathodically reduced into H 2 O 2 on carbonaceous catalysts, [238][239][240] the integration of electro-Fenton and membrane separation has drawn increasing attention to remove various organic pollutants (Fig. 6a), such as dye molecules, 241,242 persistent oxalate, 170,171 and antibiotics.…”
Section: Organic Pollutant Removalmentioning
confidence: 99%